The determinants of violent crimes and its impacts on household economic welfare in northwest Nigeria - Kurfi, Bashir Babangida (2023)
Violent crimes and armed conflicts are among the world's most significant challenges. The ongoing activities of militant groups known as "bandits" in north-western Nigeria result in massacres, sexual assaults, property crimes, kidnappings, and armed robberies, with an increasing number of victims and displaced persons. Despite the deterrent factors, violent crime has increased over the years. This raises the question of the key factors that might play a role in violent crime. This study aims to investigate the influence of deterrence factors, corruption, the rule of law, and socio-economic factors on violent crime and its consequences on household economic welfare. This study uses deterrence, rational choice, and social disorganization theories as underpinning theories. Data from 498 regular households and 558 inmates were collected using a multistage sampling technique and analyzed using binary and multinomial logit regression. The result showed a significant negative relationship between deterrence factors, corruption, the rule of law, and violent crime. The result also showed a significant negative relationship between socio-economic factors and violent crime. However, it showed a significant positive influence of drug consumption and unofficial severity of punishment on violent crimes. Similarly, the results showed a positive relationship between violent crimes and household economic welfare (declining household food consumption and loss of income). Overall, the study confirmed that corruption and the rule of law are the instrumental factors that compromise strategies to combat crime. Socio-economic factors such as family disruption, family background, unemployment, and drug consumption play an enormous role in determining violent crime in Nigeria, and violent crimes significantly affect Household's economic welfare. This research has significantly contributed to the literature as it explored the influence of both formal and informal sanctions on violent crimes and successfully developed and validated a second-order model for the economic welfare scale. The findings will also help regulatory agencies and stakeholders to formulate policies that deter people from committing crimes and improve household economic welfare. Finally, directions for future research were discussed. Enforcing the criminalization of banditry and parental neglect, fighting corruption, institutionalizing family affairs, and publicizing the enforcement campaign are recommended to the policymakers to reduce violent crimes and improve household economic welfare.